2017
DOI: 10.1111/bcpt.12894
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A Exposure Impairs Epididymal Development during the Peripubertal Period of Rats: Inflammatory Profile and Tissue Changes

Abstract: Bisphenol A (BPA) is a synthetic non-steroidal oestrogen used in the production of plastics. BPA can cause alterations in the endocrine system of human beings and animals at varied stages of development. During puberty, altered morphological, sexual behaviour and completion of the epididymal development occur. Therefore, this study aimed to evaluate the effects of BPA on epididymal development during the peripubertal period of rats. Male Wistar rats were treated with BPA via gavage at doses of 20 μg/kg or 200 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 52 publications
3
18
0
Order By: Relevance
“…A previous study by our group showed that the increase in neutrophils and macrophages after bisphenol A (BPA) exposure, a toxicant and environmental contaminant, was associated with tissue changes during epididymal development in peripubertal rats. 1 Similarly, our study showed alterations in the epididymal epithelium after both malathion treatments, and the abnormalities found may be related to the inflammatory response, which leads to tissue damage. Although the lower dose of malathion did not show an increase in inflammatory cells, we observed abnormalities in the tissue of 10 mg kg À1 malathion-treated animals.…”
Section: Discussionsupporting
confidence: 72%
“…A previous study by our group showed that the increase in neutrophils and macrophages after bisphenol A (BPA) exposure, a toxicant and environmental contaminant, was associated with tissue changes during epididymal development in peripubertal rats. 1 Similarly, our study showed alterations in the epididymal epithelium after both malathion treatments, and the abnormalities found may be related to the inflammatory response, which leads to tissue damage. Although the lower dose of malathion did not show an increase in inflammatory cells, we observed abnormalities in the tissue of 10 mg kg À1 malathion-treated animals.…”
Section: Discussionsupporting
confidence: 72%
“…Izumi et al reported that the adverse effects of BPA on sperm autogenesis in the Sertoli cells of rat testis were possibly regulated via increasing levels of inflammatory factors, such as IL-1β and IL-6 [ 30 ]. Ogo et al further showed that exposure to 200 μg/mL of BPA from PND36 to PND66 increased the expression of IL-6 in the epididymis of male Wistar rats [ 31 ]. Our current results implied that the adverse effects of perinatal BPA exposure on spermatogenesis might be related to the activation of an inflammatory response in the testis of male offspring.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, recent works deepened the previous studies, with a particular emphasis on mononuclear phagocytes and lymphocytes present at steady state. Unfortunately, only a few studies described the polymorphonuclear cells in the steady state rodent epididymis, despite their crucial role in the early steps of the pathogen recognition that initiate the immune response (Fritz & Pabst, ; Gaytan et al ., ; Majeed, ,; Hess, ; Serre & Robaire, ; Mendes et al ., ; Ogo et al ., ).…”
Section: Immune Cellsmentioning
confidence: 97%